2022
DOI: 10.1001/jamanetworkopen.2022.47431
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Patient Satisfaction With Their Patient-Physician Relationship and Completion of Bariatric Surgery by Race and Ethnicity Among US Adults

Abstract: ImportanceMetabolic and bariatric surgery (MBS) is an effective and safe treatment for obesity and its comorbidities, but less than 50% of those who are eligible and referred for MBS complete the procedure. The patient-physician relationship could be a decisive factor in the decision to complete MBS; however, this relationship has not been explored, particularly among racially and ethnically diverse populations.ObjectiveTo examine the association between patient-reported satisfaction with their patient-physici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
(123 reference statements)
0
2
0
Order By: Relevance
“…Holding private insurance predicted progression to surgery, 37,49,52 while having public insurance was associated with non-progression in samples of African-American and Hispanic patients. 69,70 In addition, participants were deterred from surgery because of insurance denial and complications, 42,54,66 with Xie et al 77 further identifying that more surgery non-completers, relative to completers, were uninsured. Around 50% of the participants in Hlavin et al's38 study also "somewhat" or "strongly agreed" that the insurance process takes too long.…”
Section: Insurance Coveragementioning
confidence: 99%
See 1 more Smart Citation
“…Holding private insurance predicted progression to surgery, 37,49,52 while having public insurance was associated with non-progression in samples of African-American and Hispanic patients. 69,70 In addition, participants were deterred from surgery because of insurance denial and complications, 42,54,66 with Xie et al 77 further identifying that more surgery non-completers, relative to completers, were uninsured. Around 50% of the participants in Hlavin et al's38 study also "somewhat" or "strongly agreed" that the insurance process takes too long.…”
Section: Insurance Coveragementioning
confidence: 99%
“…54,62,63,66 Longer wait times, in terms of time from orientation to multi-disciplinary evaluation and overall wait time to surgery, were further barriers to surgery. 24,32,33,60 Moreover, Xie et al 77 found that surgery completers reported better satisfaction with their patient-physician relationship than noncompleters.…”
Section: Social Influence and Relationshipsmentioning
confidence: 99%